The Role of Community Health Nurses in Promoting Maternal and Child - Nashar, Ali Khalid Abdullah Bin; Hanan, Thahab Ahmed Mohamed; Alshaibani, Mohammad Muslah; Awaji,HadiahQari; Knadiry, Afnan Naseer; Alomran, Salman Ibrahim; Alonayzan, Fatimah Essa; Alrwili, Mona Tobean Rasheed; Jubran, Ehab Ali Hussin; Albeladi, Ghada Ali; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Maternal and child health (MCH) is one of the pillars of health in the population, as it demonstrates the health status and progress of the nation. Community health nurses have a crucial role in MCH promotion by offering preventive health care, health education and by providing direct services to people on the grassroots level. The study aims to address the topic of The Role of Community Health Nurses in Promoting Maternal and Child Health by delving into their roles, issues, and input into the functioning of the systems of public health, The paper explains the history and importance of MCH, what is meant by community health nursing and the history of the nursing practice in the community. It emphasizes the critical functions of community health nurses in health promotion, disease prevention, prenatal and postnatal care, immunization, nutrition surveillance, and family based intervention. Moreover, it examines the international and regional issues influencing MCH and determines the obstacles to the efficiency of nurses including the lack of resources, cultural factors, and policy restrictions. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">The importance of ethical considerations, cultural sensitivity, and interprofessional cooperation are highlighted as some of the major aspects of effective community nursing. The role of health policies, evidence-based practice integration, and modern innovations, including telehealth, mobile health technology, and other innovations, that have revolutionized community care, are also discussed in the paper, the study gives recommendations and future goals of improving MCH by creating better infrastructure, ongoing training of nurses and fair health policies. The results highlight how the provision of appropriate resources, education, and support to community health nurses can help considerably decrease maternal and child morbidity and mortality. To enhance their contribution will thus be crucial in attaining universal health cover and creating healthier and more resilient societies all over the world.